Biochemical Changes in Methotrexate Users in Combination with Leflunomide for Rheumatoid Arthritis (Research, Society and Development, 2020)
Objective. To analyze the biochemical changes of patients with Teresina-PI CEAF using methotrexate monotherapy and in combination with leflunomide for the treatment of rheumatoid arthritis. Methods. The research was characterized in a cross-sectional, descriptive study, with a quantitative and qualitative approach where data collection was carried out by searching the National System of Management of Pharmaceutical Services - HORUS and through consultations of the documentary records of users assisted by CEAF based on therapeutic treatment, drug interference in laboratory parameters, treatment time, sex and changes in therapeutic treatment. All statistical analyses were performed using the Statistical Package for the Social Science (SPSS) software, to obtain these analyses we used the Mann-Whitney U test for independent variables with a 95% confidence level. For a significant result, the p-value needs to be lower than the significance level α=0.05. Results. 98 patients selected for the study, 90,81 % were female, 9.18 % male, in relation to drug treatment there were similarities with the characteristic findings, 92.85 % of these patients were using MTX + LEF with association and 7.14 % were using monotherapy with MTX. The patients in both treatment presented alterations in laboratory parameters at the two time intervals, with a greater change in liver enzymes AST/ALT in the shortest period of time, creatinine was the test that showed the least alteration, with a slight change in patients on associated treatment in the period of time greater than one year. Conclusion. In view of the analysis of the results, it was found that there was no statistically significant difference between the laboratory parameters analyzed: liver enzymes AST / ALT, hemoglobin and creatinine of patients treated with MTX in isolated therapy and with MTX associated with LEF.